FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF PADA DI WILAYAH KERJA PUSKESMAS PASIR PUTIH KABUPATEN KOTAWARINGIN TIMUR - Syahla Aryza Zaharani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
Breast milk is the best intake for babies during the first six months of life, as it contains all the nutrients necessary for optimal growth and development. This study aims to identify the factors that affect exclusive breastfeeding in the working area of the Pasir Putih Health Center, Kotawaringin Timur Regency. Using a cross-sectional study, data was collected from 104 mothers who had babies aged 6-24 months through questionnaires and tests. Data analysis was carried out using a univariate and bivariate approach (chi-square test). The results of the study showed that only 40.4% of mothers provided exclusive breastfeeding. Maternal education factors (p=0.002), maternal knowledge (p=0.000), maternal attitude (p=0.000), IMD (p=0.000), maternal health (p=0.000) and family support (p=0.000) showed a significant relationship with exclusive breastfeeding, maternal employment factors (p=0.345) and childbirth assistants (p=1,000) did not show a significant relationship with exclusive breastfeeding.